The revival of the silk roads (lands connectivity) in Asia - Rana, Pradumna B. (2014)
This paper argues that contrary to popular belief, in the bygone era, there was not one but two Silk Roads in Aisa – the Northern and the less well-known South-western Silk Road (SSR). The SSR connected South/Central Asia with southern China and present day Association of Southeast Asian nations (ASEAN). After enjoying a rich history of around 1,600 years, the Silk Roads went into disrepair. Now, for various economic, security, and political reasons, land connectivity is once again making a comeback in Asia. These include the (i) “Go West” and the recent “New Silk Roads” policies of China; (ii)”Look East” policies of South Asia; (iii)opening if Myanmar, a node between South Asia and East Asia; and (iv) growing importance of supply-chain trade. The focus has, however, been mainly on reviving the Northern Silk Road with relatively few actions being initiated to revive the SSR. Mirroring the on-going efforts in the Greater Mekong Sub-region and the Central Asian region, this paper proposes four economic corridors for Pan-Asian connectivity that is to connect South/Central Asia with south China and ASEAN. The paper argues that the revival of land connectivity in Asia is making Maritime Asia if the past, more continental-based. One implication is that regional institutions focusing solely on Maritime Asia, such as the Asia Pacific Economic Cooperation (APEC), may be losing some of their relevance vis-à-vis say the more continental-based China-led Shanghai Cooperation Organization. The other is that the influence of the West in Asia’s security may be declining relative to that of China, India, and Russia.